The state of green computing knowledge among students in a Malaysian public university - Tunku Ahmad, Tunku Badariah; Nordin, Mohamad Sahari; Bello, Abdullahi (2013)
This article reports on a study undertaken to explore the state of Malaysian university students’ knowledge of green computing. Two types of knowledge were assessed, i.e. subjective knowledge and objective knowledge. The study also sought to ascertain the influence of gender and field of study on the two types of knowledge, and whether they were positively and significantly correlated. A total of 208 students from ICT- and non-ICT study programmes of a Malaysian public university took the survey. Data were collected using a self-developed green computing questionnaire. Descriptive statistics, independent-samples t-tests and bivariate correlation were employed to analyze the data. Results show a general lack of knowledge on various aspects of green computing, particularly with respect to Energy Star, E-PEAT, Malaysia Green Techology Policy, printer types and energy consumption, energy-efficient practices and hazardous chemicals present in computers. Gender influenced perceived knowledge – with female students reporting significantly higher knowledge levels – but not objective knowledge, while field of study influenced both in favor of students pursuing ICT-related degree programmes. A significant positive correlation was discovered between the two types of knowledge. The results suggest a strong need for green computing education to be initiated across Malaysian university campuses.